Nepenthes diabolica (Nepenthaceae), a new species of toothed pitcher plant from Central Sulawesi - Bianchi, Andrea; Lee, Chien C.; Golos, Michal R.; Mey, François S.; Mansur, Muhammad; Mambrasar, Yasper Michael; Robinson, Alastair S. (Phytotaxa, 2020)
Nepenthes diabolica, a new species of tropical pitcher plant from Central Sulawesi, is described and illustrated. It is a high-montane, terrestrial to epiphytic taxon, distinguished by its elaborately flanged peristome and rufous, woolly pitcher indumentum. N. diabolica is a member of section Tentaculatae, showing morphological affinities with N. hamata. Nevertheless, the two species can be distinguished by morphological characters as well as by ecology and geography. A diagnostic key to the species of section Tentaculatae is provided. Owing to its highly restricted range, small number of recorded individuals, and desirability among plant collectors, the conservation status of N. diabolica is assessed as Critically Endangered under the IUCN criteria. Finally, N. hamata, until now based on lost types and mixed paratypes, is lectotypified using recently uncovered original material.